NMB promotes the progression of colorectal cancer by regulating the NF-κB/P65 signaling pathway - Fan, Jiaxin; Liu, Yuming; Wang, Jiajia; Yao, Tian; Bai, Shaoxiong; Ma, Xiaole; Chen, Hao; Chen, Yuhao; Gao, Huiyang; Guo, Yuntong; Huang, He (Frontiers in Immunology, 2025)
BackgroundColorectal carcinoma (CRC) ranks as the fourth most prevalent malignancy globally. Neuromedin B (NMB) and its corresponding receptor have been implicated in the pathogenesis of multiple neoplastic conditions. Nevertheless, the specific involvement of NMB in CRC progression remains poorly characterized.MethodsTo investigate the differential expression of NMB, data were extracted from the TCGA and GEO databases, supplemented by tissue microarrays derived from clinical specimens. Prognostic significance was assessed through Kaplan-Meier survival analysis, ROC curve evaluation, Cox proportional hazards regression, clinical correlation studies, and nomogram construction. Experimental validation of NMB expression in CRC was performed using qRT-PCR, western blotting, immunohistochemistry, and ELISA techniques. Functional characterization of NMB's tumor-regulatory capacity was conducted through colony formation assays, MTT proliferation tests, wound healing experiments, and transwell migration/invasion assays. Mechanistic insights were obtained by identifying upstream regulatory proteins via co-immunoprecipitation and exploring potential signaling pathways through gene set enrichment analysis (GSEA) combined with western blot validation.ResultsAnalysis of clinical data revealed that NMB exhibits markedly elevated expression levels in CRC tissues, with higher expression correlating significantly with poor prognosis. Receiver operating characteristic curve analysis validated NMB's utility as a reliable prognostic biomarker for survival outcomes. Importantly, multivariate Cox regression analysis demonstrated NMB’s independent prognostic value in CRC patients. In vitro functional studies provided compelling evidence that NMB promotes CRC cell proliferation, migration, and invasive potential. Molecular investigations uncovered that NMB protein stability is regulated through USP21-dependent deubiquitination, leading to subsequent activation of the NF-κB signaling cascade and tumor progression. Notably, NMB expression patterns showed significant correlation with 5-fluorouracil resistance profiles, indicating its potential role in mediating chemotherapeutic response in CRC treatment regimens.ConclusionNMB exhibits significant overexpression in colorectal cancer, demonstrating promising potential as a dual-functional biomarker for both diagnostic identification and prognostic evaluation in CRC cases.